Characterization of facial pain in individuals with hemifacial spasm - Soares, Míriam Carvalho; Silva, Mariana de Almeida Cruz; Albuquerque, João Augusto de Macedo Cavalcanti de; Franco, Clélia Maria Ribeiro; Filho, Pedro Augusto Sampaio Rocha (Headache Medicine, 2024)
Background Hemifacial spasm (HFS) is defined by involuntary facial contractions, more common in women in the fifth decade of life. Facial pain associated with HFS is observed in clincal practice, although there is still little research on the subject. This study aims to investigate the frequency and characterization of facial pain in HFS patients and its correlations. Objective Characterize facial pain in HFS patients. Analyze if pain was associated with clinical spasm severity, quality of life (QoL), anxiety, depression and insomnia. Methods Cross-sectional study involving 59 patients of a public hospital. Patients with cognitive impairment, use of botulinum toxin in the last three months and other movement disorders were excluded. Data were obtained using the following instruments: sociodemographic questionnaire; structured questionnaire of facial pain characteristics (intensity in a visual analog scale: VAS, frequency, location); McGill pain questionnaire; hemifacial spasm grading questionnaire (HFS-Score) for clinical severity and QoL; hospital anxiety and depression scale (HADS); and insomnia severity index (ISI). Results Among 59 patients, 39 (66.1%) were female and mean age was 65.9 years (SD: 12.9). Average diagnosis time was 15.5 years (SD: 8.5) and most common spasm side was left: 36 patients (61%). 26 patients (44.1%) reported facial pain, mean intensity was 6.1 (SD: 2) in VAS and frequency of 5 (IQR: 12) days/month. The facial pain locations were: periorbital in 21 cases (80.7%), maxillary in 5 (19.2%) and mandibular in 2 (7.6%). Auricular and whole hemiface were mentioned in 1 case (3.8%) each. 25 patients (96.1%) described pain ipsilaterally to spasm, and 1 (3.9%) described pain bilaterally. Most common descriptors for pain were: pulling (11 patients), itchy (10 patients) and annoying (10 patients). Association between facial pain and worse QoL was found (p: 0.038; Mann-Whitney test). Facial pain was related to insomnia (p: 0.037; Fisher exact test). No association was found between facial pain and clinical spasm severity, age, anxiety or depression. Conclusion This study showed a considerable frequency of facial pain in HFS patients and characterized its patterns and correlations. Explore pain symptoms in HFS patients is necessary for tailored therapeutic approaches.